2014
DOI: 10.1017/jfm.2014.633
|View full text |Cite
|
Sign up to set email alerts
|

Streamwise and doubly-localised periodic orbits in plane Poiseuille flow

Abstract: We study localised exact coherent structures in plane Poiseuille flow that are relative periodic orbits. They are obtained from extended states in smaller periodically continued domains, by increasing the length to obtain streamwise localisation and then by increasing the width to achieve spanwise localisation. The states maintain the travelling wave structure of the extended states, which is then modulated by a localised envelope on larger scales. In the streamwise direction, the envelope shows exponential lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 48 publications
7
49
1
Order By: Relevance
“…Chaotic sets developed from extended versions of these solutions clearly exhibit wave trains with a varying count of wave periods embedded (Ritter et al , to be published). This will most probably be the case for localised plane Couette and plane Poiseuille solutions too Zammert & Eckhardt 2014). The non-snaking localisation mechanism (Burke & Knobloch 2006) found in double-diffusive convection (Beaume et al 2013b) cannot apply to plane Couette, plane Poiseuille or pipe flows, as the required condition that a nontrivial streamwise-independent state exists is not fulfilled by any of these flows.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chaotic sets developed from extended versions of these solutions clearly exhibit wave trains with a varying count of wave periods embedded (Ritter et al , to be published). This will most probably be the case for localised plane Couette and plane Poiseuille solutions too Zammert & Eckhardt 2014). The non-snaking localisation mechanism (Burke & Knobloch 2006) found in double-diffusive convection (Beaume et al 2013b) cannot apply to plane Couette, plane Poiseuille or pipe flows, as the required condition that a nontrivial streamwise-independent state exists is not fulfilled by any of these flows.…”
Section: Resultsmentioning
confidence: 99%
“…This scenario has been confirmed for extended domains allowing for localisation, albeit with modifications regarding the spatial structure of the underlying solution, which is no longer periodic but localised (Mellibovsky et al 2009;Duguet et al 2009). Fully localised invariant solutions of the Navier-Stokes equations have since been found by restricting the dynamics to appropriate symmetry subspaces in long pipes (Avila et al 2013), and in extended domains (spanwise and/or streamwise) in plane Couette and plane Poiseuille flows (Zammert & Eckhardt 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, their calculation were strongly truncated and attempts to reproduce their results with better resolution failed [29]. Subsequent studies identified many other three-dimensional exact solutions for PPF [29][30][31][32][33][34]. Waleffe [35] and Nagata & Deguchi [29] studied the dependence of particular solutions on the streamwise and spanwise wavelengths.…”
Section: Three-dimensional Travelling Wavesmentioning
confidence: 99%
“…We use a numerical resolution of N x × N y × N z = 32 × 65 × 64 for small domains and increase it to N x × N y × N z = 80 × 65 × 112 for a domain with L x = L z = 4π. For sufficiently large domains the edge state of PPF is a traveling wave [33] that is symmetric with respect to the center-plane,…”
Section: Three-dimensional Travelling Wavesmentioning
confidence: 99%
See 1 more Smart Citation